Optimal weights for measuring redshift space distortions in multitracer galaxy catalogues - Pearson, David W.; Samushia, Lado; Gagrani, Praful (My University, 2016)
Since the volume accessible to galaxy surveys is fundamentally limited, it is extremely important to analyse available data in the most optimal fashion. One way of enhancing the cosmological information extracted from the clustering of galaxies is by weighting the galaxy field. The most widely used weighting schemes assign weights to galaxies based on the average local density in the region (FKP weights) and their bias with respect to the dark matter field (PVP weights). They are designed to minimize the fractional variance of the galaxy power-spectrum. We demonstrate that the currently used bias dependent weighting scheme can be further optimized for specific cosmological parameters. We develop a procedure for computing the optimal weights and test them against mock catalogues for which the values of all fitting parameters, as well as the input power-spectrum are known. We show that by applying these weights to the joint power-spectrum of emission line galaxies and luminous red galaxies from the Dark Energy Spectroscopic Instrument survey, the variance in the measured growth rate parameter can be reduced by as much as 36 per cent.
Citation: Pearson, D. W., Samushia, L., & Gagrani, P. (2016). Optimal weights for measuring redshift space distortions in multitracer galaxy catalogues. Monthly Notices of the Royal Astronomical Society, 463(3), 2708-2715. doi:10.1093/mnras/stw2177
Keywords: Methods: Data Analysis; Galaxies: Statistics; Cosmological Parameters; Large-Scale Structure Of Universe; Oscillation Spectroscopic Survey; Baryon Acoustic-Oscillations